Using and communicating uncertainty for the effective control of invasive non‐native species. (26th February 2020) - Ward, Alastair I.; Richardson, Suzanne; Macarthur, Roy; Mill, Aileen C.
Abstract: Estimates of quantities needed to plan invasive species control, such as population size, are always uncertain; this is an issue that can become a problem when mishandled in ecological science and its communication. The complexities of incorporating uncertainty into sophisticated decision‐support tools may be a barrier to their use by decision makers, leading to decisions being made without due regard to uncertainty and risking misplaced certainty of predicted outcomes. We summarise ways in which uncertainty has been incorporated into and used to advise decisions on the management of invasive non‐native species and other problem species, and offer a simple conceptual model for accommodating and using uncertainty at the planning stage. We also demonstrate how frequently uncertainty has been misused and miscommunicated in the wildlife management literature. We contend that uncertainty in estimates of natural quantities must be acknowledged, can inform decisions and can be made to derive decisions, and should not be ignored if invasive species policy is to be delivered effectively. Uncertainty must be communicated thoroughly and correctly by scientists if decision makers are to understand its consequences for planning and resourcing control programmes. Abstract : Reliable information is key to evidence‐based decision‐making and good decisions rely on a high degree of certainty. In advance of an invasion by a non‐native species, we are very uncertain about their likely future distribution, abundance, impacts and costs of control, so we may need to rely on the structured evaluation of expert opinion to prioritise invasive species for action. As an invasion progresses (invasion stages are represented here in blue boxes), more information is generated, reducing uncertainty, so it is possible to make better‐informed decisions about control (planning actions corresponding to each stage are represented in orange stars, with information flows [purple arrows] and decision points [blue arrows]). These decisions and predictions of their likely outcomes can be improved by including evaluations of uncertainty into the decision‐making process (methods for capturing and characterising uncertainty at each invasion stage are represented in green ovals). Ultimately, uncertainty cannot be completely eliminated, but it can be reduced via a process of learning‐by‐doing, termed adaptive wildlife management.